Perbandingan Kualitas Fermentasi Biji Kakao dengan Menggunakan Kultur Campur dan Kultur Tunggal Saccharomyces cerevisiae - Olsen O Pramana; Yoga Aji Handoko (Universitas Negeri Makassar, 2022)
Cocoa fermented products in Indonesia generally produce poor quality fermentation. This study was conducted to compare the quality of fermented cocoa beans with the addition of mixed and single cultures of Saccharomyces cerevisiae. This study used a randomized block design (RAK) method with 7 treatments, namely control, single culture (KT5%), (KT10%), (KT15%) and mixed culture (KC5%), (KC10%), (KC15%). Observation parameters include pH, temperature, water content, reducing sugar content, lactic acid content, acetic acid content, total fat content, cut test and organoleptic. The analytical data obtained were then analyzed with the SAS device with a further test of 0.05% BNJ. The results showed that the addition of mixed culture (KC15%) had an effect on the quality of fermented cocoa beans. The quality of fermented cocoa beans in KC15% treatment showed reducing sugar content of 6.51%, lactic acid content of 0.05%, acetic acid content of 0.79%, total fat content of 50.10%, fermented beans 78% and organoleptic results on texture. , color, aroma and distinctive taste of cocoa, resulted in a good assessment of the KC15% treatment.